Mengikis Sikap Superioritas Beragama untuk Mencapai Persatuan Indonesia - Kaleb Ginting; Simon Simon (STT Bala Keselamatan Palu, 2023)
Abstract: This paper was elaborated by the researchers because in fact there are individuals who practice religion by showing their superior attitude that their belief is more correct or they are much better than others and this is characterized by an arbitrary attitude towards other religions. This paper used a qualitative method with a literature approach. Through this writing topic, the author described about eroding the attitude of superiority as a form of the practice of Pancasila in the principle of